Configural Theory of Why People Shop for Clothes: Personal-Attribute Explanations of Four Stalwart Segments - Schuhmacher, Monika; von Janda, Sergej; Woodside, Arch (Korean Academy of Marketing Science, 2014)
The study here applies fuzzy set qualitative comparative analysis (QCA) to offer configurations that are sufficient to identify “Clotheshorses”, “Clothesaholics”, “Clothesgourmands” and “Clothesnegators”. In contrast to prior literature investigating only clothes shopping frequency, we find these four clothes shopper types are different with regard to the perceived “importance of dressing well”. The findings demonstrate the existence of these four stalwart segments.